2006
DOI: 10.1038/sj.jhh.1002116
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and cardiac dimensions among 9- to 18-year-old youth: the Québec Family Study

Abstract: The relationship between adiposity and cardiac dimensions were considered in healthy 9-to 18-year-old boys (n ¼ 198) and girls (n ¼ 154). Indicators of adiposity included the body mass index (BMI), sum of skinfolds (SSF) and trunk-to-extremity ratio (TER). The following left ventricular (LV) dimensions were measured by echocardiography: internal diameter (LVIDd); posterior wall thickness (PWT) and intraventricular septal wall thickness. LV mass (LVM) was estimated. In boys, 11 of 45 correlations were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…The importance of obesity for the different echocardiographic parameters has been controversially discussed especially concerning echocardiographic parameters of diastolic function. But in nearly all studies, indices of LV mass were greater in overweight and obese than in normal weight children or adolescents [ 39 42 ]. It should be noted that, the prevalence of left ventricular hypertrophy in overweight children varies dependent of the method used for normalization [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of obesity for the different echocardiographic parameters has been controversially discussed especially concerning echocardiographic parameters of diastolic function. But in nearly all studies, indices of LV mass were greater in overweight and obese than in normal weight children or adolescents [ 39 42 ]. It should be noted that, the prevalence of left ventricular hypertrophy in overweight children varies dependent of the method used for normalization [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Medical College of Virginia Twin Study,7 data from a group of 243 children aged 11 years showed that LVM was inversely related to suprailiac skinfold thickness in a multivariate regression model including weight, gender, systolic and diastolic blood pressures, and heart rate. Findings from the Quebec Family Study33 demonstrated that, among healthy adolescents aged 9–18 years, BMI was positively and significantly correlated with LVM in all of the six age–gender subgroups, and the sum of six skinfolds was significantly correlated with LVM in only three of the six subgroups. Details of the correlations after adjustment for body size were not described in the report.…”
Section: Discussionmentioning
confidence: 99%
“…Also, one study has shown the significance and positive correlation between BMI and LVM among healthy 9-18 year old children and teenagers in all six age and gender subgroups. [18] In another study conducted by Daniel et al ., to determine the relationship between LVM and systolic blood pressure and BMI, it was found that systolic blood pressure was associated with LVM/height indicator in a univariate analysis. Likewise, it was found that this indicator was positively associated with BMI per se .…”
Section: Discussionmentioning
confidence: 99%